Karjaan rautatieasema - Brandt , Bror
innehållsbeskrivning: Karis järnvägsstations toalett i oktober 1955.
Keywords: järnvägsstationer; toaletter; järnvägstrafik; järnvägsstationer; toaletter; Suomi, Uusimaa, Raasepori, Karjaa; Suomi, Uusimaa, Länsi-Uusimaa